(untitled) (Proceedings of Voronezh State University. Series: Geology, 2024)
Introduction: mosaic distribution of compressional and tensile areas is a fundamental property of coal-rock massif, which at great depths generates dangerous coal, rock, gas emissions and leads to accidents and human casualties in coal mining. Despite the danger, identification of compression and stretching areas is not on the list of exploration tasks. Therefore, in order to improve the safety of coal mining, the development of a formation geobarometer is an urgent issue. Methodology: the development of the geobarometer consisted in algorithmizing the process of using geological-genetic and thermodynamic models of gas content, as well as in its testing in one of the mine fields. These models were built by establishing the relationship of gas content with a certain factor under the condition of constancy of other factors. The minimum number of factors was justified by means of causal analysis of previously proposed factors. Based on the analysis of the geological structure and availability of the necessary initial data, the fields of coal mines A.A. Skochinskii and Sukhodolskaya-Vostochnaya were selected as objects of research. Results and discussion: the graphs of gas content change depending on the degree of metamorphism and reduction of coals were constructed. Using these graphs, the geological and genetic model of gas content of clarenaceous coals of Donbass was constructed. On the basis of the Langmuir equation the thermodynamic model of gas content was developed, describing the change of gas content with depth. These models are the basis for the development of a reservoir geobarometer. Testing of the geobarometer confirmed its ability to detect anomalously high and low gas pressure and its superiority to trivial gas-bearing models. Conclusion: a reservoir geobarometer has been developed, which allows to distinguish the baric component from the general variation of coal gas content on the basis of geological-genetic and thermodynamic models of gas content. The geological-genetic model of gas content is based on the main factors determining the sorption capacity of organic matter, represented by metamorphism, reduction and maceral composition of coals. The thermodynamic model developed on the basis of the Langmuir equation reflects the influence of external conditions on gas sorption by organic matter, the generalizing indicator of which is the depth of the reservoir. Testing of the reservoir geobarometer confirmed its ability to determine anomalously high and low reservoir pressure, as well as to identify anomalous methane accumulations and degassing channels in the section.